Tree Circumference Changes and Species-Specific Growth Recovery After Extreme Dry Events in a Montane Rainforest in Southern Ecuador - Raffelsbauer, Volker; Spannl, Susanne; Peña, Kelly; Pucha-Cofrep, Darwin; Steppe, Kathy; Bräuning, Achim (Frontiers in Plant Science, 2019)
Under drought conditions, even tropical rainforests might turn from carbon sinks to sources, and tree species composition might be altered by increased mortality. We monitored stem diameter variations of 40 tree individuals with stem diameters above 10 cm belonging to eleven different tree genera and three tree life forms with high-resolution dendrometers from July 2007 to November 2010 and additionally March 2015 to December 2017 in a tropical mountain rainforest in South Ecuador, a biodiversity hotspot with more than 300 different tree species belonging to different functional types. Although our study area receives around 2200 mm of annual rainfall, dry spells occur regularly during so-called “Veranillo del Niño” (VdN) periods in October-November. In climate change scenarios, droughts are expected with higher frequency and intensity as today. We selected dry intervals with a minimum of four consecutive days to examine how different tree species respond to drought stress, raising the question if some species are better adapted to a possible higher frequency and increasing duration of dry periods. We analyzed the averaged species-specific stem shrinkage rates and recovery times during and after dry periods. The two deciduous broadleaved species Cedrela montana and Handroanthus chrysanthus showed the biggest stem shrinkage of up to 2 mm after 10 consecutive dry days. A comparison of daily circumference changes over 600 consecutive days revealed different drought responses between the families concerning the percentage of days with stem shrinkage/increment, ranging from 27.5% / 72.5% for Graffenrieda emarginata to 45% / 55% for Podocarpus oleifolius under same climate conditions. Moreover, we found great difference of recovery times after longer-lasting (i.e., eight to ten days) VdN drought events between the two evergreen broadleaved species Vismia cavanillesiana and Tapirira guianensis: While Vismia replenished to pre-VdN stem circumference after only five days, Tapirira needed 52 days on average to restore its circumference. Hence, a higher frequency of droughts might increase inter-species competition and species-specific mortality and might finally alter the species composition of the ecosystem.